Evaluation of the effects of short-term PM2.5 exposure on triglyceride-glucose metrics in a population in eastern China - Zhenpeng Guo; Chenchen Yang; Qiang Zhang; Xinling Shi; Xiaona Li; Qun Zhang; Jianming Wang (BMC Cardiovascular Disorders)
Abstract Context The triglyceride-glucose (TyG) index, a novel health indicator, has been widely employed to assess insulin resistance (IR). However, its relationship with fine particulate matter (PM) exposure remains inadequately investigated. Objective This study endeavors to probe the association between PM2.5 and TyG within the population of eastern China and to determine whether there are disparities in this association among diverse subgroups. Methods We conducted an ecological study on a cohort comprising 39,011 individuals who had undergone at least two physical examinations between 2017 and 2019 at the First Affiliated Hospital of Nanjing Medical University, China. TyG levels concerning short-term PM2.5 exposure were examined using a generalized additive model. Results In the overall population, at lags of 0–7 and 0–14 days in the single-pollutant model, it was observed that a 10 µg/m3 rise in PM2.5 corresponded to a 0.0021 elevation in TyG levels. In the multi-pollutant models, at 0–7 and 0–14 days lags, a comparable increase in PM2.5 resulted in an increase in TyG of 0.0073 and 0.0044, respectively. The association remained significant in the subgroup analyses. Conclusion PM2.5 exposure is related to the TyG index. Controlling air pollution might contribute to maintainin normal lipid metabolism function.